Remedial Module with Augmented Reality Application and IoT Monitoring for Remedial Students - Ayub, Afiq Azim; Sirat, Norfatanah; Jaafar, Marliana; Mat Akir, Rohaida; Ilyas, Mohammad Arif; Othman, Maisara (Multidisciplinary Applied Research and Innovation, 2021)
This trend shows that more students and teachers switch or adapt the learning method from a direct close-up in class into a whole virtual online style. This internet of things technology can interact and connect with all electronic devices, thus reducing the inaccessibility gap towards other people far away from us. Remedial Education Program (REP) is the initiative from the Ministry of Education (MOE) Malaysia that focus on helping remedial students that have a problem in reading, writing, and counting. Inside REP, the main crucial subjects in this program are the Bahasa Melayu, English, and mathematics. As for this case, the Bahasa Melayu is the one that will highlight. Remedial teachers that well train use the Guidebook as one of their sources to teach remedial students to overcome their problems. The objective is to create and analyze the effectiveness application towards remedial students and store and monitor the data results of that learning application through the cloud. Remedial Module Augmented Reality (ReModAR) application has two main menus for the remedial students to learn while playing with the modules which are the Pembelajaran and Pengujian. ReModAR idea comes from the collaboration with remedial teachers in the selected area around Batu Pahat, Johor, and PPD Batu Pahat. REP needs a new interactive platform to cater to a different method to teach remedial students. ReModAR learning application has a conducive system of interactions that any user can use. Support for the android platform, ReModAR can easily be downloaded and install for any devices that use the Android platform in general. Increasing the learning capability with the aid of psychomotor will guarantee the enhancement of remedial students learning and understanding. This learning application’s friendly interface is easy to understand for the remedial students and kindergarten or usual primary school students.